The Effect of Religiosity, Rule Compilance, and Machiavellian Nature on Fraudulent Behaviour - Avilya Baysta Bheda Wea; Sisilia Rachel Ari Putri (Journal of Accounting and Auditing, 2025)
Purpose – This study aims to examine how religiosity, rule compilance and machiavellian nature affect fraudulent behaviour. Design/methology/approach – This study use quatitative research methods, using primary data collected from population of 110 education institusions for teachers and education personnel. Data analysis was conducted using Partial Least Square (PLS) software SEM adaptation 3.0. Fidings – This comes about discover that religiosity does not essentially influence cheating behaviour and is within the same heading as the theory which implies it is in understanding with the theory, rule recognition does not altogether influence fraudulent behaviour and is within the same direction as the theory which suggests it is in undertanding with the hypothesis, whereas unscrupulous nature essentially influences fraudulent behaviour and in within the same course as the theory which implies it is in understanding with the hypothesisi. Research limitation/implication – This study discusses cheating behavior and the factors that influence it in the Merry Riana Group company. This research is centered on cheating behavior, where this research may be a study that examines the relationship between religiosity, rule observance and machiavellian traits in carrying out consent performances, immoral characteristics of cheating behavior